Discrete Subaortic Stenosis in an Elderly Patient. Issue 1 (June 2021) - Dey, Jaideep; Akhtar, Nadeem; Shama, Vivek; Mustaqueem, Arif; Shrivastava, Sameer
Discrete subaortic stenosis is an uncommon condition in the elderly population. Echocardiographic examination can be useful for diagnosis with high accuracy. We present a case report of an elderly female patient who presented with accelerated hypertension and was subsequently diagnosed with discrete subaortic stenosis on transthoracic echocardiography. A significant, non-dynamic, left ventricular outflow tract pressure gradient in the presence of aortic regurgitation should raise the possibility of this condition in patients of geriatric age group.